Sistem Informasi Administrasi Perkantoran pada Badan Kesatuan Bangsa dan Politik Kabupaten XYZ - Sukmawati Sukmawati; Marwan M. Londol; I Gusti Putu Rika Permana; Agustince A. Lesak; Wibowo. K, Trisno (Lembaga Pengembangan Kinerja Dosen, 2025)
Correspondence administration is a crucial element in supporting smooth communication, coordination, and documentation within the government. Every government agency, including the Banggai Islands National Unity and Politics Agency (Kesbangpol), requires orderly and systematic correspondence administration to ensure timely delivery and proper documentation. Kesbangpol Banggai Islands plays a strategic role in political coordination, fostering national insight, and facilitating inter-agency communication, making the existence of an effective correspondence administration system crucial. Currently, the management of incoming and outgoing mail is still carried out manually. This manual process creates various obstacles, including the risk of document loss, delays in information distribution, recording errors, and difficulties in searching archives. In addition, the manual system limits transparency and accountability, as it is often difficult to accurately track the flow of documents. This condition can certainly hamper organizational performance and reduce the quality of public services. This research aims to design and build an integrated correspondence administration information system based on digital technology. The system is designed to improve efficiency, effectiveness, and accuracy in document management, ensuring that every incoming and outgoing letter is properly recorded and easily accessible. The research methods used include needs analysis, system design, implementation, and testing. The expected outcome of this study is the development of a digital solution that simplifies the process of recording, searching, and reporting official letters. With this system, it is hoped that the Banggai Islands Kesbangpol will be able to improve organizational performance by accelerating communication and documentation flows. Furthermore, the implementation of this system will also support the principles of transparency, accountability, and modernization of public services within the local government. Ultimately, the implementation of an integrated information system will not only reduce administrative errors but also foster better governance and public trust.